Translation and Validation of the Basic Psychological Need Satisfaction in Active Commuting to and from School (Bpns-Acs) Scale in Young Portuguese Students - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Active commuting to and from school (ACS) is a strategy to enhance physical activity levels in youths. To promote ACS, it is important to understand the factors that lead to this behaviour. With this in mind, an adaptation of the Basic Psychological Needs in Exercise Scale for ACS was developed, named the Basic Psychological Need Satisfaction in Active Commuting to and from School (BPNS-ACS) scale. This study aimed to translate and evaluate the psychometric properties of the BPNS-ACS scale in young Portuguese students. A cross-sectional study was designed. A total of 338 students (212 girls, 126 boys), aged between 11 and 19 years old from 31 Portuguese cities participated in this study. To provide validity evidence based on the questionnaire’s internal structure, confirmatory factor analyses were performed to test the three dimensions of the BNPS-ACS scale. The results of the confirmatory factor analysis indicated an acceptable fit to the data. The internal consistency of the measures was accepted as the composite reliability values ranged from 0.78 to 0.94. The evaluation of psychometric properties provided evidence of the adequacy of this questionnaire among Portuguese youth aged 11 to 19 years old. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.